Malnutrition alters protein expression of KNDy neuropeptides in the arcuate nucleus of mature ewes - Thorson, Jennifer F.; Prezotto, Ligia D. (Frontiers in Physiology, 2024)
The neuropeptides kisspeptin, neurokinin B, and dynorphin A are imperative for the pulsatile secretion of gonadotropin-releasing hormone and luteinizing hormone to ultimately regulate reproductive cyclicity. A population of neurons co-expressing these neuropeptides, KNDy neurons, within the arcuate nucleus of the hypothalamus (ARC) are positioned to integrate energy status from afferent neuronal and glial cells. We hypothesized that KNDy-expressing neurons in the ARC of mature ewes is influenced by energy balance. To test this hypothesis, ovary-intact, mature ewes were fed to lose, maintain, or gain body weight and hypothalamic tissue harvested during the luteal phase of the estrous cycle. Fluorescent, multiplex immunohistochemistry with direct antibody conjugation was employed to identify and quantify neurons expressing a single neuropeptide, as well as for the first time report co-expression of kisspeptin, neurokinin, and dynorphin protein in the ARC. Previous reports using this population demonstrated that concentrations of insulin and leptin differed between ewes fed to achieve different body weights and that ewes fed to gain body weight had increased concentrations of progesterone. Moreover, within this population of ewes tanycyte density and cellular penetration into the ARC was increased in ewes fed to gain body weight. Within the current report we have revealed that the number of neurons in the ARC expressing kisspeptin, neurokinin B, and dynorphin protein was increased in ewes fed to gain body weight. Moreover, the number of KNDy neurons in the ARC expressing all three neuropeptides within a single neuron was decreased in ewes fed to lose body weight and increased in ewes fed to gain body weight when compared to ewes fed to maintain body weight. The cumulative findings of this experimental model suggest that expression of kisspeptin, neurokinin B, and dynorphin protein in the ARC during the luteal phase of the estrous cycle are influenced by energy balance-induced alterations in circulating concentrations of progesterone that drive changes in morphology and density of tanycytes to ultimately regulate central perception of global energyetic status.Moreover, these results demonstrate that changes in KNDy neurons within the ARC occur as an adaptation to energy balance, potentially regulated divergently by metabolic milieu via proopiomelanocortin afferents.